2012
DOI: 10.1111/adb.12008
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in decreased limbic and cortical grey matter volume in cocaine dependence: a voxel‐based morphometric study

Abstract: Structural neuroimaging studies have provided evidence of differences in local brain volume between cocaine-dependent and healthy control individuals. While sex differences in aetiology, course and brain dysfunction associated with chronic cocaine abuse have been previously documented, evidence of sex-specific differences in brain volume has not been examined thus far. This study examined sex-related differences in grey matter volume between cocaine-dependent and healthy control subjects using voxel-based morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
4
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 51 publications
5
48
4
6
Order By: Relevance
“…Authors of some studies (15)(16)(17) primarily have recruited men to exclude the confounding effects of sex, and other investigators (2,18,19) have not included sex as a factor in their analyses of gray matter in patients with stimulant dependence. In fact, to our knowledge, only two studies (20,21) have included descriptions of structural differences between the sexes in patients with stimulant dependence. Rando et al (21) reported lower GMV in the left inferior frontal medial frontal gyrus, anterior cingulate gyrus, insula, and nucleus accumbens in patients with stimulant dependence (2,3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors of some studies (15)(16)(17) primarily have recruited men to exclude the confounding effects of sex, and other investigators (2,18,19) have not included sex as a factor in their analyses of gray matter in patients with stimulant dependence. In fact, to our knowledge, only two studies (20,21) have included descriptions of structural differences between the sexes in patients with stimulant dependence. Rando et al (21) reported lower GMV in the left inferior frontal medial frontal gyrus, anterior cingulate gyrus, insula, and nucleus accumbens in patients with stimulant dependence (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, to our knowledge, only two studies (20,21) have included descriptions of structural differences between the sexes in patients with stimulant dependence. Rando et al (21) reported lower GMV in the left inferior frontal medial frontal gyrus, anterior cingulate gyrus, insula, and nucleus accumbens in patients with stimulant dependence (2,3). In the largest meta-analysis of stimulant dependence to date, Ersche et al (2) reported significant decreases in gray matter in the insula, ventromedial prefrontal cortex, inferior frontal gyrus, anterior cingulate gyrus, and anterior thalamus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta‐analysis of 9 studies and 296 alcohol dependent individuals found significantly reduced prefrontal gray matter (GM) volumes, including anterior cingulate cortex (ACC) [Xiao et al, 2015], with frontal cortical GM volume being negatively associated with lifetime alcohol use [Taki et al, 2006]. Prefrontal GM volumes were similarly reduced in cocaine dependent individuals, including in orbitofrontal cortex (OFC) [Rando et al, 2013; Tanabe et al, 2009], anterior prefrontal cortex [Rando et al, 2013] and ACC [Connolly et al, 2013], the latter associated with years of drug use [Connolly et al, 2013]. …”
Section: Introductionmentioning
confidence: 99%
“…However, findings regarding the volumes of the amygdala and hippocampus in cocaine-dependent patients are less consistent. One study reported increased volume in the amygdala (Ersche et al, 2012), several studies reported reduced volume in at least one of the two structures (Alia-Klein et al, 2011; Makris et al, 2004; Moreno-Lopez et al, 2012; Rando et al, 2013), and several studies did not find volumetric differences (Jacobsen et al, 2001; Narayana et al, 2010; Sim et al, 2007); reviewed in (Mackey and Paulus, 2013)).…”
Section: Introductionmentioning
confidence: 99%